Color tunable dual-phase transparent glass ceramics for warm white light-emitting diodes. Issue 3 (5th January 2017) - Chen, Daqin; Xu, Wei; Zhou, Yang; Zhong, Jiasong; Li, Shichen
Abstract : Currently, Ce 3+ :Y3 Al5 O12 phosphor converted white light-emitting diodes suffer from a deficiency of adequate red components and easy aging of the organic silicone matrix. Abstract : Currently, Ce 3+ :Y3 Al5 O12 phosphor converted white light-emitting diodes suffer from a deficiency of adequate red components and easy aging of the organic silicone matrix. Herein, Ce 3+ /Mn 2+ /Si 4+ :Y3 Al5 O12 phosphors were synthesized via a traditional solid-state reaction and they can emit intense red luminescence, which is attributed to the Mn 2+ : 4 T1 → 6 A1 spin-forbidden transition under the excitation of blue light via efficient energy transfer from Ce 3+ to Mn 2+ . Temperature-dependent emission spectra and luminescent decay curves evidence that Mn 2+ activators partition into both the Al 3+ octahedral and Y 3+ dodecahedral sites, whereas the Si 4+ sites located in the Al 3+ tetrahedral site are charge compensators. Furthermore, inorganic Ce 3+ :Y3 Al5 O12 and Ce 3+ /Mn 2+ /Si 4+ :Y3 Al5 O12 dual-phase transparent glass ceramics were successfully fabricated via a low-temperature co-sintering technique to replace the phosphor in organic silicone as a color converter, and red to yellow tunable luminescence can be easily achieved by controlling the content of red phosphor in the glass matrix. Note that by combining the fabricated dual-phase glass ceramics with the InGaN blue chip, warm white light-emitting diodes with a superior optical performance and excellent heat-resistance stability were successfully constructed.